Characterization of unintentional doping in nonpolar GaN - Zhu, Tongtong; Johnston, Carol F.; Häberlen, Maik; Kappers, Menno J.; Oliver, Rachel A. (Journal of Applied Physics)
Unintentional doping in nonpolar a-plane 112¯0 gallium nitride GaN grown on r-plane 11¯02 sapphire using a three-dimensional 3D–two-dimensional 2D growth method has been characterized. For both 2D only and 3D–2D growth, the presence of an unintentionally doped region adjacent to the GaN/sapphire interface is observed by scanning capacitance microscopy SCM. The average width of this unintentionally doped layer is found to increase with increasing 3D growth time. By using an intentionally doped GaN:Si staircase structure for calibration, it is shown that the unintentionally doped region has an average carrier concentration of 2.50.31018 cm−3. SCM also reveals the presence of unintentionally doped features extending at 60° from the GaN/sapphire interface. The observation of decreasing carrier concentration with distance from the GaN/sapphire interface along these features may suggest that the unintentional doping arises from oxygen diffusion from the sapphire substrate. Low temperature cathodoluminescence spectra reveal emission peaks at 3.41 and 3.30 eV, which are believed to originate from basal plane stacking faults BSFs and prismatic stacking faults PSFs, respectively. It is shown that the inclined features extending from the GaN/sapphire interface exhibit both enhanced BSF and PSF emission. We suggest that enhanced unintentional doping occurs in regions around PSFs. Where BSFs intersect this doped material their emission is also enhanced due to reduced nonradiative recombination. Transmission electron microscopy confirms the presence of PSFs extending through the film at 60° from the GaN/sapphire interface.

Defects in carbon implanted silicon calculated by classical potentials and first-principles methods - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, Jörg; Schmidt, W. G.; Rauls, E. (Physical Review B)
A comparative theoretical investigation of carbon interstitials in silicon is presented. Calculations using classical potentials are compared to first-principles density-functional theory calculations of the geometries, formation, and activation energies of the carbon dumbbell interstitial, showing the importance of a quantummechanical description of this system. In contrast to previous studies, the present first-principles calculations of the interstitial carbon migration path yield an activation energy that excellently matches the experiment. The bond-centered interstitial configuration shows a net magnetization of two electrons, illustrating the need for spin-polarized calculations.

Advanced topics and applications of Transmission Electron Microscopy, Part I-II - Lindner, Jörg

Ion Beams and Nano-Engineering

Dislocation reduction in MOVPE grown GaN layers on (111)Si using SiNxand AlGaN layers - Häberlen, M; Zhu, D; McAleese, C; Kappers, M J; Humphreys, C J (Journal of Physics: Conference Series)
Growth of GaN on Si(111) potentially enables cost efficient manufacturing of optoelectronic devices due to the possibility of using cheap large area substrates. However, GaN layers grown on Si(111) substrates suffer from high tensile stress that can lead to cracking at layer thicknesses exceeding 1 μm. Another challenge is the high dislocation density of GaN layers grown on Si(111) which is detrimental to device performance. In this paper we show that a step graded AlGaN buffer layer can compensate tensile stress, avoiding cracking, and at the same time reduce the dislocation density. An additional SiNx interlayer in the GaN layer is shown to further reduce the dislocation density down to the high 108 /cm². Weak beam dark field TEM was used to study the dislocation reduction in cross sectional samples and for comparison of the step graded AlGaN buffer layer structure to a continuously graded one. STEM ADF was used to determine the exact location of dislocation bending with respect to the position of the interface.

Dislocation reduction in GaN grown on Si(111) using a strain-driven 3D GaN interlayer - Häberlen, Maik; Zhu, Dandan; McAleese, Clifford; Zhu, Tongtong; Kappers, Menno J.; Humphreys, Colin J. (physica status solidi (b))
In this paper we demonstrate a strain-driven GaN interlayer method to reduce dislocation densities in GaN grown on (111) oriented silicon by metal organic vapour phase epitaxy (MOVPE). In order to achieve crack-free GaN layers of reasonable thicknesses and dislocation densities it is crucial to integrate both dislocation reduction and strain management layers. In contrast to techniques like FACELO or nanoELO we show the in situ formation of GaN islands directly on the AlN nucleation layer without the need to deposit a SiO2 or SiNx mask. A graded AlGaN layer for strain management can be grown on top of this dislocation reducing 3D GaN inter-layer in order to achieve crack-free GaN layers grown on top of the AlGaN strain management layer. Furthermore, an additional SiNx layer for subsequent dislocation reduction can also be incorporated into the structure and is shown to efficiently reduce the dislocation density down to the low 10^9 cm^2. The structural properties of the 3D GaN island buffer layer and overgrown samples are studied by means of SEM, cross-sectional, and plan view TEM. Cathodoluminiscence in an SEM is employed to correlate the dislocation microstructure as observed by plan view TEM with luminescent properties.

Low temperature photoluminescence and cathodoluminescence studies of nonpolar GaN grown using epitaxial lateral overgrowth - Häberlen, M.; Badcock, T. J.; Moram, M. A.; Hollander, J. L.; Kappers, M. J.; Dawson, P.; Humphreys, C. J.; Oliver, R. A. (Journal of Applied Physics)
Low temperature cathodo- and photoluminescence has been performed on nonpolar a-plane GaN films grown using epitaxial lateral overgrowth. In films overgrown at a low V–III ratio, the emission spectrum is dominated by “yellow” and “blue” luminescence bands, attributed to recombination at point defects or impurities. The intensity of this emission is observed to decrease steadily across the window region along the −c direction, possibly due to asymmetric diffusion of a point defect/impurity species. When overgrown at a higher V–III ratio, the near band edge and basal-plane stacking fault emission intensity increases by orders of magnitude and a donor–acceptor pair band is observed. Using monochromatic cathodoluminescence imaging, the various emission features are correlated with the microstructure of the film. In particular, the peak energy of the basal-plane stacking fault emission is seen to be blueshifted by 15 meV in the wing relative to the window region, which may be related to the different strain states in the respective regions.

The effects of annealing on non-polar (112¯0) a-plane GaN films - Hao, Rui; Zhu, T.; Häberlen, M.; Chang, T.Y.; Kappers, M.J.; Oliver, R.A.; Humphreys, C.J.; Moram, M.A. (Journal of Crystal Growth)
Non-polar a -plane (1 1 2 ̄ 0) GaN films were grown on r-plane sapphire by metal–organic vapor phase epitaxy and were subsequently annealed for 90 min at 1070°C. Most dislocations were partial dislocations, which terminated basal plane stacking faults. Prior to annealing, these dislocations were randomly distributed. After annealing, these dislocations moved into arrays oriented along the [0 0 0 1] direction and aligned perpendicular to the film–substrate interface throughout their length, although the total dislocation density remained unchanged. These changes were accompanied by broadening of the symmetric X-ray diffraction 1 1 2 ̄ 0 w-scan widths. The mechanism of movement was identified as dislocation glide, occurring due to highly anisotropic stresses (confirmed by X-ray diffraction lattice parameter measurements) and evidenced by macroscopic slip bands observed on the sample surface. There was also an increase in the density of unintentionally n-type doped electrically conductive inclined features present at the film–substrate interface (as observed in cross-section using scanning capacitance microscopy), suggesting out-diffusion of impurities from the substrate along with prismatic stacking faults. These data suggest that annealing processes performed close to film growth temperatures can affect both the microstructure and the electrical properties of non-polar GaN films.

Fine Structure of Triplet Centers in Room Temperature Irradiated 6H-SiC - Scholle, Andreas; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
In non-annealed 6H-SiC samples that were electron irradiated at room temperature, a new EPR signal due to a S=1 defect center with exceptionally large zero-field splitting (D = +652·10-4 cm-1) has been observed under illumination. A positive sign of D demonstrates that the spin-orbit contribution to the zero-field splitting exceeds by far that of the spin-spin interaction. A principal axis of the fine structure tilted by 59° against the crystal c-axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin-orbit coupling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

Modellbasierte Bestimmung lokal gültiger Kinetiken chemischer Reaktionen in Flüssigphase mittels Flachbettmikroreaktor* - Warnecke, H.-J.; Bothe, D.; Zrenner, Artur; Berth, Gerhard; Hüsch, K.-P. (Chemie Ingenieur Technik)
Strömungsbasierte Mischprozesse sind grundlegender Bestandteil vieler chemischer Prozesse. Realisierbare Mischzeiten reichen von einigen Millisekunden bis zu Sekunden, wobei die vollständige Homogenisierung oft nicht sichergestellt ist. Werden kinetische Parameter chemischer Reaktionen dieses Zeitskalenbereichs ohne Berücksichtigung der Mischprozesse bestimmt, sind sie mischungsmaskiert und geben die inhärente chemische Kinetik nicht wieder. In dieser Arbeit wird die Validierung und Anwendung einer Methode zur Bestimmung inhärenter chemischer Kinetiken von in Flüssigphase ablaufenden chemischen Reaktionen im stationären, laminaren Flachbettmikroreaktor vorgestellt. Der verfolgte Ansatz basiert auf der mechanistischen Modellierung der Molmengen unter Berücksichtigung von Konvektion, Diffusion und Reaktion und der Bestimmung der unbekannten Parameter durch Anpassung des Modells an experimentell ermittelte Konzentrationsverläufe.